Flavorubredoxin, a Candidate Trigger Related to Thrombotic Thrombocytopenic Purpura: Screening of the Complete Genome of a Salmonella enterica Serovar Typhimurium Isolate From an AIDS Case - Wang, Zhouhan; Xu, Hao; Gu, Beiqing; Jin, Yanqi; Wang, Tianyuan; Ma, Jindi; Lu, Yingfeng; Yu, Xiaopeng; Zheng, Beiwen; Zhang, Yimin (Frontiers in Cellular and Infection Microbiology, 2022)
Thrombotic thrombocytopenic purpura (TTP) is one of the two classic thrombotic microangiopathy (TMA) diseases which could be induced by infections. To the best of our knowledge, this is the first report of an acquired immunodeficiency syndrome (AIDS) patient with acquired TTP induced by infection with Salmonella enterica serovar Typhimurium (hereafter, S. Typhimurium) isolate, S. Typhimurium_zhang, which was confirmed by serology and genetic taxonomy. The literature review identified 17 TMA-related genes encoding the candidate triggers, which were searched in the annotated genome sequence of S. Typhimurium_zhang. Anaerobic nitric oxide reductase flavorubredoxin (FlRd), encoded by norV, which is related to another TMA, haemolytic uraemic syndrome (HUS), was found in S. Typhimurium_zhang. Basic local alignment search tool (BLAST) analysis revealed that norV and FlRd in S. Typhimurium_zhang, as well as eight S. Typhimurium type strains, have high identity with HUS-related Escherichia coli O157:H7 strain TW14359. Similar results were obtained from the BLAST analysis of 73 S. enterica isolates for congenital TTP, which was also previously reported to be triggered by S. enterica. Phylogenetic analysis and amino acid sequence alignment revealed that FlRd was functional and highly conservative on 69 Enterobacteriaceae, including S. Typimurium_zhang and TW14359. In brief, we found norV in the genome of a S. Typhimurium clinical isolate that induced TTP in an AIDS patient. FlRd, the protein encoded by norV, probably triggered the TTP and was highly conservative, functional, and widespread in S. enterica and Enterobacteriaceae. More in vitro and in vivo studies are required to confirm our findings and determine the underlying mechanism.